Impact of Internal Mammary Artery Harvesting on Sternal Healing: A Review - Yahya, Taufik Nur; Ismail, Naufal Arif (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Internal mammary artery (IMA) is the preferred conduit for coronary artery bypass grafting (CABG) due to its superior long-term patency. However, its harvesting disrupts sternal vascularization, potentially leading to impaired sternal healing and complications such as sternal wound infection (SWI). This review aims to synthesize current evidence on how IMA harvesting affects sternal healing after CABG, with a focus on surgical techniques, patient risk factors, and postoperative complications. Objective: This review aims to provide a comprehensive synthesis of current evidence regarding the impact of IMA harvesting on sternal healing following CABG. Methods: A review was conducted using the PubMed and ScienceDirect databases, including studies published from 2015 to 2025. Studies published before 2015 were considered if they provided foundational knowledge and were relevant. Randomized controlled trials (RCTs), propensity studies, and observational studies analyzing IMA harvesting techniques and sternal healing were included. The primary outcomes assessed were SWI, non-union, and delayed healing. Results: A total of 13 studies met the inclusion criteria, comprising 6 observational studies, 3 propensity-matched studies, and 4 RCTs. Bilateral IMA grafting was associated with an increased risk of SWI, especially in diabetic and obese patients. However, skeletonized IMA harvesting was linked to improved sternal perfusion and reduced wound complications compared to pedicled techniques. Additionally, interventions such as continuous insulin infusion and low-level laser therapy showed promise in enhancing sternal healing outcomes. Conclusion: IMA harvesting impacts sternal healing, particularly in high-risk patients undergoing bilateral IMA grafting. Skeletonized harvesting techniques and optimized perioperative care can mitigate the risk of complications.